Redefining Early Childhood Growth and Development Surveillance: A Sustainable, Technology-Integrated Primary Care Ecosystem Linking Maternal Health Literacy, Digital Monitoring, and Predictive Analytics - Suryadinata, M Agus; Girma, Abel; Tiwari, Shyam Sundar; Mpemba, Faraja (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to analyze the relationships between maternal health literacy, digital monitoring utilization, growth and development surveillance behavior, and early developmental risk detection among mothers of toddlers.Methodology: A mixed-methods sequential explanatory design was employed at Arosbaya Public Health Center, Bangkalan, Indonesia. The quantitative phase involved a cross-sectional survey of 210 mothers with children under five years old. Data were analyzed using structural equation modeling–partial least squares (SEM-PLS) to examine relationships among variables. The qualitative phase consisted of in-depth interviews with mothers, healthcare workers, and community health volunteers to provide contextual explanations for the quantitative findings. Thematic analysis was used to interpret qualitative data.Main Findings: Maternal health literacy significantly influenced digital monitoring utilization (β = 0.54, p < 0.001) and surveillance behavior (β = 0.32, p = 0.002). Digital monitoring utilization significantly affected surveillance practices (β = 0.41, p < 0.001) and early developmental risk detection (β = 0.29, p = 0.004). Growth and development surveillance behavior demonstrated the strongest association with early risk detection (β = 0.46, p < 0.001). Qualitative findings revealed mothers who possessed higher health literacy were more capable of interpreting child development information and were more likely to utilize digital tools for monitoring their children’s growth.Novelty/Originality of this study: This study integrates maternal health literacy, digital monitoring utilization, and child growth surveillance behavior within a mixed-methods framework, providing a multidimensional understanding of early developmental risk detection in primary healthcare settings.